Multiple Pleistocene refugia in the Brazilian cerrado: evidence from phylogeography and climatic nichemodelling of two Qualea species (Vochysiaceae) - Buzatti, Renata Santiago de Oliveira; Lemos-Filho, José Pires; Bueno, Marcelo Leandro; Lovato, Maria Bernadete (Botanical journal of the Linnean Society, 2017)
Abstract The cerrado is a large savanna in central Brazil, which extends north to the Amazon Forest and the caatinga (xeric vegetation) and includes disjunct areas in both of those biomes. Cerrado plant diversification is understudied, especially in disjunct areas and in peripheral areas bordering other biomes. Here we investigated the effects of Quaternary climatic fluctuations on the distribution, genetic diversity and divergence of two closely related species, Qualea multiflora and Qualea parviflora. Both species are widely distributed in the cerrado, including disjunct and peripheral areas. We sequenced plastid DNA from individuals of both species across their distributions, including core, disjunct and peripheral areas of the cerrado. Both species showed similar responses to Quaternary climatic fluctuations with range retractions during the Last Glacial Maximum (LGM). Phylogeographic analyses and ecological niche modelling revealed a large historical glacial refugium across central Brazil and multiple refugia in peripheral areas of the south-west, north-west (bordering the Amazon) and north-east (in transition with the caatinga). The genetic diversity, diversification and geographical structuring of Q. multiflora and Q. parviflora were mainly shaped by Pleistocene climatic fluctuations. The presence of several refugia at the Amazon Forest boundary suggests that savanna vegetation could have covered parts of the south-western Amazon during the LGM.